2017
DOI: 10.4103/0973-1296.210127
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to extraction methods in recovery of capsaicin from habanero pepper (CNPH 15.192)

Abstract: Introduction:The objective of this study was to compare three capsaicin extraction methods: Shoxlet, Ultrasound-assisted Extraction (UAE), and Shaker-assisted Extraction (SAE) from Habanero pepper, CNPH 15.192.Materials and Methods:The different parameters evaluated were alcohol degree, time extraction, and solid–solvent ratio using response surface methodology (RSM).Results:The three parameters found significant (p < 0.05) were for UAE and solvent concentration and extraction time for SAE. The optimum conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
1
4
1
1
Order By: Relevance
“…Additionally, thermal processing improved significantly (p<0.05) the TPC in all cases, obtaining the highest values of TPC for samples added with LEO in pastes of both ripening stages. According to Martins et al (2017), the dehydration of a food matrix may improve phenolic compound extraction by the disruption of the cellular matrix and the increase of compounds bioavailability. Additionally, the cleavage and subsequent oxidation of capsaicinoids in the thermal processing leads to the formation of vanillin, which could be used to produce other substituted phenols associated with TCC (Perucka & Materska, 2003;Pino et al, 2011).…”
Section: Tpc and Antioxidant Activitymentioning
confidence: 99%
“…Additionally, thermal processing improved significantly (p<0.05) the TPC in all cases, obtaining the highest values of TPC for samples added with LEO in pastes of both ripening stages. According to Martins et al (2017), the dehydration of a food matrix may improve phenolic compound extraction by the disruption of the cellular matrix and the increase of compounds bioavailability. Additionally, the cleavage and subsequent oxidation of capsaicinoids in the thermal processing leads to the formation of vanillin, which could be used to produce other substituted phenols associated with TCC (Perucka & Materska, 2003;Pino et al, 2011).…”
Section: Tpc and Antioxidant Activitymentioning
confidence: 99%
“…The effect of solid‐to‐solvent ratio ( x 1 ), temperature ( x 2 ), and time ( x 3 ) on the extraction process of bioactive compounds from habanero pepper were evaluated as independent variables following a Box–Behnken design performed by Design Expert Program 6.0.6 (StatEase Inc., Minneapolis, MN). The range and central point of the three independent variables (Table 1) were chosen according to preliminary experiments and the results obtained by Martins et al (2017) who indicated that as the extraction time and the solid‐to‐solvent ratio increase, the capsaicin yield increases. A Box–Behnken design results in 20 experiments, including 15 different experiments and 6 replicates of the central point (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, some studies about capsaicin extraction from habanero pepper have indicated that both the fruit part (shell and seed) and the extraction time significantly affect the extraction of this bioactive compound (Chinn et al, 2011). Moreover, Martins et al (2017) indicated that among technologies used for extracting capsaicin from the habanero pepper, Soxhlet displayed the higher extraction, followed by the ultrasound‐assisted and agitation extraction methods. Moreover, no significant difference ( p > .05) in capsaicin yield was observed between the last two extraction methods, with the advantage of higher stability (compared with Soxhlet extraction) during short time storage (6 hr).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the extraction conditions, the extraction yield, quality, and bioactivity of the extracted compounds is affected. The most extensively used method to recover capsaicinoids is based on the extraction with hexane, which is very toxic and produces residues that could compromise the quality of the compounds (Martins et al, 2017). However, various extraction methods for capsaicinoids have been developed expanding the extraction solvents alternatives to methanol, ethanol, acetonitrile, and water (Lu et al, 2017).…”
Section: Technological Advances For the Extraction Of Capsaicinoidsmentioning
confidence: 99%